Plasma prothrombin time and activated partial thromboplastin time as predictors of bleeding manifestations during dengue hemorrhagic fever - I. N. Budastra; B. N. P. Arhana; IB. Mudita (Paediatrica Indonesiana, 2009)
Background  Massive bleeding and shock are complications  ofdengue  hemorrhagic  fever (DHF)  that  are associated withhigh mortality. Impaired hemostasis, especially coagulopathy,contributes  to  bleeding manifestations in DHF. Parameters suchas  activated partial thromboplastin time (APTT)  and  plasmaprothrombin  time (PPT) indicate  the  impact  of  coagulationsystem.Objective  To  determine the relationship between  APTT  and PPTlevels with bleeding manifestations in  DHF  patients.Methods  A prospective  cohort  study was applied to subjectsdiagnosed with  DHF  at  the  Infection  and  Tropical DiseasesDivision, Department  of  Child Health, Medical School, UdayanaUniversity, Sanglah Hospital, Denpasar, Indonesia. Laboratorytests  to  determine  APTT  and  PPT  were carried  out  on  thethird, fourth,  and  fifth day after  the  onset  of  fever. Bleedingmanifestations were examined in patients during their hospitalstay. Univariate  and  Cox regression analyses were performedto examine relationship between  APTT  and  PPT  values withbleeding manifestations in  DHF  patients.Results  Forty-three children were enrolled in this study.  Therewas a significant relationship between increases in  APTT  valuewith bleeding manifestations in  DHF  patients [RR 2.79 (95%CI1.68 to 4.69), P <0.01]. Cox regression analysis showed  that  onlyincreased  APTT  values correlated with bleeding manifestations[RR 2.05 (95%CI 1.92 to 3.90), P  =  0.02].Conclusion  APTT  values may be used  as  a predictor for bleedingmanifestations  in  DHF.